The suitability of native application for university e-learning compared to web-based application - Sari, Maya Novia; Mohamad Ali, Noor Azian (International Journal of Science and Research, 2015)
The evolution of mobile market has pushed organization and application developers to always catching up with the latest innovation of mobile technology. In terms of mobile application architecture, it is always been a dilemma whether to build an application as a native application or web-based application. This paper discusses about the suitability of mobile application architecture for educational purpose applications such as e-learning. It will focus on native application with a comparison of web-based application. This paper also discusses the importance of hybrid development approach as an alternative strategy in the development of mobile application.